Kontestasi Pemikiran Islam Indonesia Kontemporer - Azra, Azyumardi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
Carool Kersten. 2015. Islam in Indonesia: The Contest for Society, Ideas and Values, London: Hurst & Company, pp. 373+xx.Comprehensive studies of contemporary Indonesian Islam are still scarce. Most of the studies on this subject deal with certain aspects of current developments in Indonesian Islam. Kersten’s book is an attempt to present an intellectual history of contemporary Indonesian Islam in six chapters: first, secularism, pluralism and liberalism in Indonesia; second, Islam in Indonesia today: discourses and interlocutors; third, the weight of predecessors: adaptations, critique, and transformation; fourth, debating secularism: Islam, statehood and democracy; fifth, the letter or the spirit of Islamic law?: legal formalists versus substantivitst; sixth, contentious triangulation: religious pluralism, human rights and freedom of thought. This book can be considered as a sequel to the Indonesian part of the book written by the same author, Cosmopolitans and Heretics: New Muslim Intellectuals and the Study of Islam (2011).DOI: 10.15408/sdi.v23i1.2905